The Influence of Thickener Addition on Filter Cake Formation During Dewatering of Mineral Suspensions - Jäder Jerker; Järnström Lars (Applied Rheology, 2003)
A novel method to continuously measure the rate of build-up of an immobilised layer (apparent filter cake) was demonstrated for three mineral suspensions containing carboxymethyl cellulose and polymer latex. These suspensions were designed to be similar to those normally used as coating colours within the paper industry. The instrumentation was based on a rheometer equipped with units for controlling (and measuring) the normal forces acting on the rotating upper plate and precise measurements of the gap height in parallel–plate geometry. The bottom plate in the measurement cell was perforated and connected to vacuum, giving the driving pressure for flow through the filter. The technique should so far be taken as a qualitative, but is an attractive method for measuring filtration in thin films under controlled shear rate. The technique enables the apparent filter cake height to be calculated at any time during dewatering of the coating colours.